The search for ancient life on Mars using morphological and mass spectrometric analysis: an analog study in detecting microfossils in Messinian gypsum - Sellam, Youcef; Gruchola, Salome; Tulej, Marek; Keresztes Schmidt, Peter; Riedo, Andreas; Meddane, Sofiane; Wurz, Peter (Frontiers in Astronomy and Space Sciences, 2025)
Hydrated sulfate deposits have been detected on Mars. A spaceflight instrument capable of detecting microfossils in these salt deposits is highly important for the search for ancient life on Mars. This study employed a range of analytical methods, including nondestructive optical microscopy and SEM-EDX, as well as spatially resolved laser ablation mass spectrometry (LIMS), the latter being designed for in-situ analyses on planetary surfaces, to comprehensively examine the morphology, texture, mineralogy, and geochemistry of fossil-bearing gypsum deposits from Algeria. These extensive gypsum formations formed during the Messinian Salinity Crisis (MSC) and serve as excellent astrobiological analogs for the large-scale hydrated sulfate deposits detected on Mars. Significant research on Messinian gypsum reveals notable microbial fossil filaments. This study aims to determine whether optical microscopy and LIMS measurements together can detect fossil filaments in the gypsum samples, identify their composition, and decipher their biogenicity and syngeneity. Spatially resolved depth profiling and chemical mapping analysis of one representative fossil filament using LIMS provided detailed mineralogical and compositional variations that correlate with distinctive morphological features. These findings collectively indicate that the fossil filament exhibits distinct composition and diagenetic processes in comparison to the surrounding gypsum host. The microfossil’s syngeneity and biogenicity were established based on the presence of morphological biosignatures, biologically relevant elements, and biologically induced or influenced minerals such as dolomite and clay minerals. The formation of these minerals within the physico-chemical context of ancient Martian lakes was also discussed. The same suite of measurements and techniques could be applied to study microfossil-bearing gypsum formations on Mars and beyond.